The effects of Astragalus, Epimedium, and Fructus Ligustri Lucidi extract on the antioxidant capacity, and immune status of goslings under stress conditions - Qu, Qing; Sun, Yihong; Liang, Yayan; Nie, Yongsheng; Gao, Ming; Yuan, Yaohui; Wang, Wei; Zhou, Shuo (Frontiers in Veterinary Science, 2025)
With the development and improvement of the scale, intensification, and production level of the goose farming industry, oxidative stress often occurs during the process of producing meat geese. This study employed the intraperitoneal injection method with a concentration of 2.96 mmol/mL H2O2 to establish a model of oxidative stress in goslings. The effects of Astragalus, Epimedium, and Fructus Ligustri Lucidi (AEF) extract on the immune function, antioxidant capacity, meat quality, intestinal morphology, and intestinal barrier integrity of goslings were investigated. Twenty-four 1-month-old Magang geese from the same batch were randomly divided into four groups: control group (C group), AEF treatment group (AEF group), H2O2 stress group (S group), AEF and H2O2 stress group (S + AEF group). The experiment lasted for 30 days, during which the AEF group and the S + AEF group were fed 0.1 g/mL of AEF aqueous solution, once daily. Hydrogen peroxide (H2O2) was employed as the stressor. On the 25th day of the experiment, the goslings were weighed and administered an abdominal cavity injection of H2O2. The results showed that compared with the control group, the body weight, spleen weight, bursa index of fabricius, spleen index, thymus index, the activity of glutathione peroxidase (GSH-PX), total superoxide dismutase (T-SOD), and catalase (CAT) in serum, liver, and jejunum were decreased in S group (p < 0.05). Meanwhile, compared with the S group, the body weight, spleen weight, bursa index of fabricius, spleen index, thymus index, the activity of glutathione peroxidase (GSH-PX), total superoxide dismutase (T-SOD), and catalase (CAT) in serum, liver, and jejunum were enhanced in S + AEF group and S + AEF + LP group (p < 0.05). However, the content of cortisol (CORT) and blood glucose were increased in S group (p < 0.05), AEF and AEF + LP effectively alleviated these growth trend. Supplementing with AEF and LP post-stress alleviated stress-induced the expression of inflammatory factors (TGF-β, TNF-α, IL-1β, IL-6), and improve L*, a*, b*, Ph45 (min), Ph24 (h) and drip loss in pectoral (p < 0.05). The intestinal morphology results showed that the villus structures in the duodenum and jejunum of goslings were short and sparse under stress conditions, with a significant decrease in the villus height/crypt depth ratio (Vh/Cd). After AEF treatments, the villus height increased, leading to an improved Vh/Cd in the small intestine. In conclusion, AEF can enhance the immune performance, and antioxidant capacity of goslings, thereby improving intestinal health. These findings offer new insights into enhancing immune performance and preventing stress in goslings.